Comparison of the renal response of bortezomib-based induction and conventional regimen in multiple myeloma patients with renal failure - Sarici, Ahmet; Kaya, Emin; Erkurt, Mehmet Ali; Berber, Ilhami; Tanriverdi, Lokman Hekim; Bahcecioglu, Omer Faruk; Gok, Selim; Kuku, Irfan (Annals of Medical Research, 2021)
Aim: Vincristine-doxorubicin-dexamethasone (VAD) was the commonly used first-line treatment for multiple myeloma (MM) patients with renal failure before bortezomib entered clinical practice. In this trial, we aimed to compare the effect of VAD and bortezomib-cyclophosphamide-dexamethasone (VCD) chemotherapy regimens on improving kidney function in MM patients with renal failure. Materials and Methods: The records of MM patients in our center between January 2010 and February 2020 were retrospectively analyzed. Patients who received VAD or VCD as a first treatment chemotherapy protocol and whose initially estimated glomerular filtration rate (eGFR) was 50 mL/min/1.73 m2 and below were included in the study. Patients were divided into two groups according to the chemotherapy regimens they received. Results: Sixty one MM patients (VAD: 26, VCD: 35) were included in the study. No significant difference was found between the VAD and VCD groups when the baseline, 1st and 2nd month eGFRs were compared (p>0.05). Overall renal response rate (at least minor response) in the VCD group at the end of the 1st month were higher than in the VAD group (p=0.002). Also, renal response rate in the VCD group at the end of the 2nd month were higher than in the VAD group (p=0.033). Conclusion: In MM patients with renal insufficiency, overall renal response rates have increased with the use of VCD instead of VAD as a standard induction regimen.